2011
DOI: 10.1071/mf10271
|View full text |Cite
|
Sign up to set email alerts
|

Similar life history traits in bull (Carcharhinus leucas) and pig-eye (C. amboinensis) sharks

Abstract: Appropriate management strategies for coastal regions require an understanding of how ecological similarities and differences among species shape ecosystem processes. Here, we tested whether morphological similarity equated to similar age and growth patterns in two common coastal sharks in northern Australia. Vertebrae of 199 pig-eye (Carcharhinus amboinensis) and 94 bull (C. leucas) sharks were sourced principally from commercial fisheries operating along the Northern Territory coastline during 2007-2009. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 43 publications
3
36
1
Order By: Relevance
“…For example, Clua et al (2013) observed adult bull sharks as the shark species responsible for the killing of an exhausted blue whale calf after entering this same area. Fishing efforts in the numerous rivers along the west coast of New Caledonia revealed several small juvenile bull sharks providing evidence that localised pupping occurs which is consistent with other studies showing female's return to rivers or estuaries, probably for pupping (Tillet et al 2011;Werry et al 2011). Females may also remain close to rivers for feeding purposes but display divergent behaviours.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, Clua et al (2013) observed adult bull sharks as the shark species responsible for the killing of an exhausted blue whale calf after entering this same area. Fishing efforts in the numerous rivers along the west coast of New Caledonia revealed several small juvenile bull sharks providing evidence that localised pupping occurs which is consistent with other studies showing female's return to rivers or estuaries, probably for pupping (Tillet et al 2011;Werry et al 2011). Females may also remain close to rivers for feeding purposes but display divergent behaviours.…”
Section: Discussionsupporting
confidence: 74%
“…Adult males may remain offshore, while pregnant females may return to rivers to pup (Werry et al , 2012Tillett et al 2012). Recent studies have also shown a Corresponding author: jwerry@oc-research.com the use of coastal habitats for older and larger bull sharks (Brunnschweiler and Baensch 2011;Tillet et al 2011;Werry et al 2011;Hammerschlag et al 2012), but the literature examining the movement patterns of adult bull sharks is rare, especially regarding their behaviours away from shallow coastal areas. Whether more oceanic habitats should be considered as essential for this species is uncertain due to the paucity of data.…”
Section: Introductionmentioning
confidence: 99%
“…We regarded the change of angle caused by differences in growth rate from intra-uterine to post-natal life history stages as the point of birth, or birth mark and recorded it as year zero (Cailliet & Goldman 2004). Annual growth band deposition has been confirmed for bull sharks (Branstetter & Stiles 1987, Neer et al 2005) and pig-eye sharks (Tillett et al 2011a).…”
Section: Methodsmentioning
confidence: 79%
“…We regarded the change of angle caused by differences in growth rate from intra-uterine to post-natal life history stages as the point of birth, or birth mark and recorded it as year zero (Cailliet & Goldman 2004). Annual growth band deposition has been confirmed for bull sharks (Branstetter & Stiles 1987, Neer et al 2005) and pig-eye sharks (Tillett et al 2011a).Preliminary study. Initial analyses determined (1) the concentric manner in which the calcareous vertebral matrix was deposited and the corresponding 3-dimensional structure of the sagittal section, and (2) inter-vertebral variation in chemical composition of the matrix.…”
mentioning
confidence: 95%
“…occupying the East Alligator River (n = 5); these were stored frozen. Maturity was determined from previously described age structure and growth dynamic assessments (Tillett et al 2011a). Sex, total weight (TW) total length (TL) and fork length (FL) were collected when possible from dead specimens.…”
Section: Sample Collectionmentioning
confidence: 99%